Optimasi Mobilitas Urban Melalui Perencanaan Komprehensif Dan Pendanaan Kreatif Untuk Jaringan MRT Di Surabaya - Kusuma Haratama; Christian Hadhinata; Endro Wibisono (Universitas Dr. Soetomo, 2024)
Surabaya is one of the largest metropolitan cities in East Java where the density of activity increases due to daily movement from surrounding cities. Congestion in the city of Surabaya, especially during peak hours, reaches alarming levels with the impact of air pollution and significant financial losses. Therefore, planning and financing rail-based public transportation, especially the Surabaya Mass Rapid Transit (MRT), is a solution that can have a direct and indirect positive impact on society, with a focus on route planning. Surabaya MRT route planning was based on 10 principles of reliable and efficient public transportation route planning, while a literature review was used to explore the potential for creative funding for the provision of these facilities. The research results show that five routes are needed to realize the Surabaya MRT service system with one central hub and five supporting hubs. Creative funding involving the private sector is recommended so as not to burden the State Budget